2014
DOI: 10.1177/0002764214534662
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Political Trust in Spain and Portugal

Abstract: This article deals with the problem of the increasing distrust in institutions in European democracies, paying special attention to countries such as Spain and Portugal, which are being severely harmed by the current economic crisis and the austerity measures imposed by supranational organizations such as the European Union and implemented by their respective national governments. Contrary to the purely political-economic paradigm, the present article, based on panel survey data gathered during the years 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(78 citation statements)
references
References 72 publications
1
45
0
5
Order By: Relevance
“…Moreover, the Spanish adhere to a profile of low interest in politics and a relatively low perception of internal and external political efficacy (Bonet et al, 2006: 118). In contrast, the preference for democracy is very high (Torcal, 2014).…”
Section: Between Participation and Expertsmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the Spanish adhere to a profile of low interest in politics and a relatively low perception of internal and external political efficacy (Bonet et al, 2006: 118). In contrast, the preference for democracy is very high (Torcal, 2014).…”
Section: Between Participation and Expertsmentioning
confidence: 94%
“…As many other South European countries, two of the most salient features of Spanish political culture have been distrust in the political institutions and indifference towards politics. Popular distrust facing political institutions followed a dramatic upward trend in the period 1980-2012 (Torcal, 2014). Moreover, the Spanish adhere to a profile of low interest in politics and a relatively low perception of internal and external political efficacy (Bonet et al, 2006: 118).…”
Section: Between Participation and Expertsmentioning
confidence: 99%
“…Una de ellas es el impacto de la crisis económica de 2008, que para algunos países del sur de Europa, ha supuesto una critical juncture (Morlino y Raniolo, 2017: 4;Rifà, 2017). Otros estudios subrayan que las actitudes hacia la política de las nuevas generaciones presentan alguna diferencia frente las de cohortes anteriores (life-cycle effects) (Llera, 2016;Torcal, 2014;Urquizu, 2016).…”
Section: Instituciones No Responsables Y Opinión Públicaunclassified
“…Hetherington 1998, p. 791), and it has been shown that trust in different political institutions is an "interrelated" and "unidimensional" concept. Therefore, a low level of political trust in a country usually goes together with low levels of trust in the diverse political institutions of that country (José R. Montero, Sonja Zmerli, and Ken Newton 2008;Mariano Torcal 2014). On the other hand, the existence of a high level of political trust would improve the reliability of the specific political institutions of that nation, which could propel good democratic and economic performance.…”
Section: Political Trust Economic Performance and The Great Recessimentioning
confidence: 99%
“…Second, the economic crisis and the restrictive political measures that were applied by the different Spanish governments have affected the welfare perceptions and political attitudes of the Spanish society Caballero and Álvarez-Díaz 2015), and political dissatisfaction has emerged through several social movements and general strikes in Spain (Caballero 2014). The resulthas been that, between 2008 and 2012, "the increase of distrust among citizens in Spain rose from 22.9% to 51.1% for the national parliament, from 53.8% to 77.7% for political parties, from 52.8% to 76.4% for politicians" (Torcal 2014).…”
Section: Political Trust Economic Performance and The Great Recessimentioning
confidence: 99%